THE ROLE OF MEDIA IN PROMOTING TRANSPARENCY OF HAJJ FUNDS: A PUBLIC RELATIONS STRATEGY ANALYSIS OF THE MINISTRY OF RELIGIOUS AFFAIRS IN CONSTRUCTING PUBLIC COMMUNICATION - Raysa Finarik Rambe; Rifqi Prayogi Hidayat; Muhammad Syarif Harefah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study explores the media relations strategies employed by the Ministry of Religious Affairs in managing the transparency of public information related to Hajj funds. In the context of increasing demands for openness highlighted by recent audit findings from the Supreme Audit Agency (BPK), which revealed weaknesses in the internal control system concerning the management of Hajj funds amounting to IDR 613.51 billion public communication has become a crucial aspect in maintaining public trust. The objective of this research is to analyze the Ministry’s strategic public relations approaches in disseminating Hajj financial information effectively and accountably through various media channels. Using a qualitative approach with a descriptive-analytical method, data were collected through literature review, documentation, and scholarly sources. The findings indicate that the Ministry of Religious Affairs has adopted a multichannel communication strategy integrating conventional media, social media, and digital platforms to address the growing demand for public transparency. This strategy also marks a shift from reactive to proactive communication in response to issues such as adjustments in the Hajj Pilgrimage Operational Costs (BPIH). The study further reveals that media serve a strategic role as partners in disseminating transparent and educational information. However, key challenges remain, including the complexity of financial information, low levels of digital literacy, and the spread of inaccurate information via social media. As a solution, this study proposes an integrated communication model based on five key elements: proactive communication, two-way digital interaction, strategic media partnerships, community education, and feedback systems. Through an interpretive approach, the research provides both theoretical and practical contributions to the enhancement of government public communication, particularly on sensitive issues such as the management of Hajj funds, which involves broad public trust and interest.